2018
DOI: 10.1080/07481187.2017.1390503
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality/religiosity’s influence on college students’ adjustment to bereavement: A systematic review

Abstract: Bereavement is prevalent among college students and spirituality/religiosity may play an important role in their bereavement adjustment. This is the first systematic review to investigate the spirituality/religiosity's relationship with bereavement among college students. We searched 10 databases and screened 598 studies. Eight studies met the inclusion criteria. Findings suggested a favorable association of spirituality/religiosity with desirable bereavement adjustment outcomes (growth, spiritual wellbeing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Systematic reviews of studies on S/R and bereavement have identified S/R as a potential resource in coping with the loss of a loved one (Becker et al 2007;Wortmann and Park 2008;Hai et al 2018), although authors note the limited number of these studies and questionable research methods in some of them. Because of the multidimensional nature of S/R, scientific literature currently does not provide answers and explanations about how different dimensions of S/R interact with the bereavement process.…”
Section: S/r During Bereavementmentioning
confidence: 99%
“…Systematic reviews of studies on S/R and bereavement have identified S/R as a potential resource in coping with the loss of a loved one (Becker et al 2007;Wortmann and Park 2008;Hai et al 2018), although authors note the limited number of these studies and questionable research methods in some of them. Because of the multidimensional nature of S/R, scientific literature currently does not provide answers and explanations about how different dimensions of S/R interact with the bereavement process.…”
Section: S/r During Bereavementmentioning
confidence: 99%
“…This includes beliefs in the afterlife, acceptance of uncontrollability and the unknown or trusting God’s will. Holding onto spiritual beliefs and values can be a positive coping strategy during bereavement [ 28 , 29 , 56 ]. The impact of facing death and experiencing challenging feelings of grief after the suicide of a loved one seem to require more than rational thoughts and understanding of feelings.…”
Section: Discussionmentioning
confidence: 99%
“…The strengthened spirituality, intuition, a feeling of support from a Higher power and experiencing a continuing bond with the deceased helped the participants cope with complicated feelings of grief. Studies reveal that higher religiosity and positive spiritual/religious coping are related to better bereavement outcomes [28,29,56,57]. The sense of presence and continuing the bond with the deceased as an outer figure can be helpful during bereavement to assure the existence of the afterlife with a hope to meet again and not lose the connection to the loved one [6,8,23].…”
Section: Spirituality Is a Supportive Resource That Can Be Reached Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…And, as described in a qualitative study by Mohamed Hussin et al (2018), bereaved Muslim parents in Malaysia indicated that they found their religion helpful in coping with their loss. Reviewers of the literature on religiosity/spirituality and bereavement have concluded that religiosity is often associated with more favorable outcomes (Becker et al, 2007;Hai et al, 2018;Wortmann & Park, 2008).…”
Section: Religiosity Is Often Associated With Better Bereavement Outc...mentioning
confidence: 99%